Modern Georgian national identity and formation of a political nation - Abesadze, Guram; Abesadze, Nodar (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
In the present scientific work, the modern Georgian national identity and the problem of the formation of a political nation are studied. During the research, the comparative research method, the spatial and temporal analysis of the systemic and structural-functional and political situation is mainly used. The modern world order has made the formation of national identity a topical issue. Modern Georgian identity is undergoing a transformation according to the new time. The role of national identity is particularly important in the political transition. It is a dimensional criterion of modern Georgian statehood. The most important condition for a modern democratic transition is the formation of a political nation. Georgian political space is polarized, which hinders the formation of a political nation. State consciousness must become a characteristic feature of the nation. Achieving national consolidation and integration remains a problem. A special role in the formation of a political nation is played by the actors of the political space. The formation of a consolidated democracy depends on their political culture and intellect. In the conditions of political polarization and institutional vacuum, the Georgian Orthodox Church has a clear position; Its functions in the political space are growing even more.